Scanning probe microscopy of adsorbed molecules on boron nitride and graphene monolayers - Pollard, Andrew J. (2010)
In this thesis, a study of a range of functional surfaces formed in ultra-high vacuum (UHV) conditions using primarily scanning probe microscopy is presented. The construction of a combined scanning tunnelling and atomic force microscope, and the experiments performed using this instrument, are also detailed.